Mapping the Proteome of Barrel Medic (Medicago truncatula) - Watson, Bonnie S. (American Society of Plant Biologists, 2003)
A survey of six organ-/tissue-specific proteomes of the model legume barrel medic (Medicago truncatula) was performed. Two-dimensional polyacrylamide gel electrophoresis reference maps of protein extracts from leaves, stems, roots, flowers, seed pods, and cell suspension cultures were obtained. Five hundred fifty-one proteins were excised and 304 proteins identified using peptide mass fingerprinting and matrix-assisted laser desorption ionization time-of-flight mass spectrometry. Nanoscale high-performance liquid chromatography coupled with tandem quadrupole time-of-flight mass spectrometry was used to validate marginal matrix-assisted laser desorption ionization time-of-flight mass spectrometry protein identifications. This dataset represents one of the most comprehensive plant proteome projects to date and provides a basis for future proteome comparison of genetic mutants, biotically and abiotically challenged plants, and/or environmentally challenged plants. Technical details concerning peptide mass fingerprinting, database queries, and protein identification success rates in the absence of a sequenced genome are reported and discussed. A summary of the identified proteins and their putative functions are presented. The tissue-specific expression of proteins and the levels of identified proteins are compared with their related transcript abundance as quantified through EST counting. It is estimated that approximately 50% of the proteins appear to be correlated with their corresponding mRNA levels.